The Myth of Decolonization and the Global South - Waheed, Ahmed W. author. (orcid)0000-0002-3591-0771 Link aut Link
XX, 251 p. 13 illus., 12 illus. in color.
Keywords: “This work displays serious critical decolonial scholarship and erudition. What also distinguishes this important book is its elegant presentation…. It is not only a pleasure to read but an enlightening work. I have nothing but praise for it.” — Professor Sabelo J. Ndlovu-Gatsheni, Chair of Epistemologies of the Global South, University of Bayreuth, Germany “The Myth of Decolonization and the Global South is a searing work of critical deconstruction… A brilliant addition to the growing body of decolonial IR… Highly recommended.” — Professor Richard Jackson, Leading Thinker Chair in Peace Studies, The University of Otago, New Zealand “In focusing on how Pakistani international relations remain hostage to the coloniality of knowledge and power, Waheed skillfully shifts the point of reference of most international relations scholarship towards the Global South.” — Professor Manuela Boatcă, Head of School of the Global Studies Programme at the University of Freiburg, Germany “The Myth of Decolonization and the Global South brilliantly unpacks and analyses the epistemic conditions that shape the possibilities and the limitations of the decolonization agenda in International Relations beyond the West.” — Dr. Somdeep Sen, Associate Professor, Department of Social Sciences and Business, Roskilde University, Denmark This book explores the coloniality of power and knowledge in Pakistan through an examination of Pakistani International Relations. It not only unveils the hegemonic processes embedded within the western capitalist structures of knowledge production but also explores how the eurocentrism of International Relations in Pakistan is sustained and maintained through a coloniality of knowledge and power which is designed to promote western epistemologies and emulate western standards. This book, consequently, provides a view of epistemic oppression from below. Ahmed W. Waheed, Ph.D. (Queen Mary University of London) is the Executive Director of ROADS Initiative, Pakistan and an Honorary Research Fellow at the School of Policy and Global Affairs, City St. George’s University of London. He is the author of the books The Wrong Ally: Pakistan’s State Sovereignty under US Dependence and Constructing ‘Pakistan’ through Knowledge Production in International Relations and Area Studies.